The Influence of Gifted and Talented Programs on Students' Self-concept - Ghina Kalaji; Nadera Alborno (Athens Institute for Education and Research, 2023)
The purpose of this research is to explore the influence of high school gifted and talented (GT) programs on students' self-concept from the students' perspectives in the UAE. A qualitative, exploratory, interview-based study was employed to answer the following question: How gifted and talented programs influence students' self-concept? Data were collected using semi-structured interviews. Ten GT students from grades 8-12 were interviewed from three different GT programs in UAE schools. Analysis revealed that students exhibited positive self-concept in three dimensions: general, academic, and social. The GT programs in the UAE seem to influence students' self-concept positively by nurturing their strengths, valuing their efforts, developing their skills, and emphasizing their future roles in the community.